FINANCIAL LITERACY, BEHAVIORAL INTENTION, AND THE ADOPTION OF MOBILE BANKING USAGE IN JAMBI CITY - Mardiana R; Irfan Hasandi; Mira G Pangestu; Effiyaldi; Intan Nuraini (Jurnal Riset Bisnis, 2026)
This study investigated factors that influence the behavioral intention to use mobile banking among users in Jambi City. This study used a quantitative research design and the data were gathered from 392 participants through a structured questionnaire. The analysis, conducted using multiple linear regression, confirmed that performance expectancy, effort expectancy, social influence, facilitating conditions, and financial literacy each have a significant positive impact on the behavioral intention to use mobile banking, both individually and collectively. Research findings show that the adoption of mobile banking is a complex process influenced by a blend of perceived utility, ease of use, social factors, technological support, and the user's financial knowledge. This study contributes to the existing collection of literature on digital financial service adoption by emphasizing the need for financial institutions to develop comprehensive strategies that address both the technological and educational aspects of mobile banking to encourage wider use